The density of barnyard grass affects photosynthesis and physiological characteristics of rice - X.L. WANG; Z.Y. ZHANG; X.M. XU; G. LI (Photosynthetica, 2019)
Barnyard grass (Echinochloa crus-galli) is a troublesome graminaceous weed infesting rice fields in the Yangtze River Basin, China. However, the effects of barnyard grass on rice root physiology are unclear. In this study, the effects of barnyard grass, planted at different densities (ranging from 2-8 plants m-2), on rice performance were evaluated, including chlorophyll fluorescence parameters, Rubisco activity, root oxidation activity, and the zeatin + zeatin riboside concentration. The results indicated that rice photosynthesis and physiological characteristics decreased as the density of barnyard grass increased. The rice net photosynthetic rate significantly declined and ranged between 17.3-10.5% compared with the control (0 barnyard grass plants m-2). The results showed that rice grain yields decreased to 58% when barnyard grass was planted at a density of 8 plants m-2. We found that barnyard grass can reduce the Rubisco activity, leaf photosynthetic capacity, and energy conversion efficiency in rice, thus resulting in the reduced rice yield.